Pengaruh Brandt Daroff Exercise Terhadap KeluhanPusing Pada Lanjut Usia Dengan Vertigo - Farida, Farida, Umi Budi Rahayu, S.Fis., M.Kes (2017)
Background: Vertigo is not a disease but a symptom of the disease. In the elderly the process of degeneration of the vestibular system can lead to a disease that is benign paroxysmal positional vertigo (BPPV) in the form of dizziness. This occurs because the particles of calcium carbonate present in the macula of the utricle apart so that entry into the semicircular canal and stimulate the gravity sensor then convey false signals to the brain giving rise to vertigo and dizziness. Level headache sufferer benign parosyxmal positional vertigo can be measured by visual vertigo analogue scale (VVAS) which has a score with three categories, 0-3 mild dizziness, 4-6 moderate dizziness and 7-10 severe dizziness. Objective: To determine the effects of brandt daroff exercise there of to complaints of dizziness in elderly with vertigo. Benefit Research: To determine the effects of brandt daroff exercise to complaints of dizziness in elderly with vertigo. Method: This research used is a quantitative research, using Quasi-Experimental approach and design Two Groups Pre And Post Test Design With Control Group Design. The sampling technique is Purposive Sampling with a sample of 123 people. Measurement dizziness using Visual Vertigo Analogue Scale (VVAS) by adding up the value of the whole question. Statistical test using the parametric test T Independent. Results: Based on the statistical test known that p-value 0,007<0,05 then H0 is rejected and Hα accepted. So that it can be interpreted that there is the effects of brandt daroff exercise to complaint of dizziness in elderly with vertigo. Conclusion: There is the effects of brandt daroff exercise to complaint of dizziness in elderly with vertigo. Key Word: Brandt daroff exercise, dizziness, elderly, benign paroxysmal positional vertigo, vertigo.